(untitled) (The Review of Diabetic Studies, 2025)
Background: Postoperative pain management has traditionally relied on opioids, which carry significant risks of adverse effects and long-term dependence. This has prompted the exploration of novel opioid-sparing techniques to provide effective analgesia while minimizing opioid exposure. This study aimed to evaluate the effectiveness of a multimodal opioid-sparing protocol in reducing postoperative pain and opioid consumption. Methods: A prospective, comparative study was conducted with 120 patients undergoing elective surgery. Participants were randomly assigned to either an opioid-sparing intervention group (n=60) or a conventional opioid-based control group (n=60). The intervention group received a tailored multimodal protocol combining pharmacological agents (e.g., NSAIDs, acetaminophen, gabapentinoids), regional anesthesia, and non-pharmacological interventions. Primary outcomes included postoperative pain intensity measured on a visual analog scale (VAS) and opioid consumption recorded in morphine milligram equivalents (MME). Results: The opioid-sparing group demonstrated significantly lower pain scores at all measured time points (e.g., immediate postoperative VAS: 3.2 vs. 5.6, p<0.001). Opioid consumption was reduced by more than 50% in the intervention group (mean MME 18.4 vs. 42.7). Furthermore, the incidence of opioid-related side effects (nausea, vomiting, constipation, sedation) was markedly lower, and patient satisfaction was significantly higher in the opioid-sparing group. Conclusion: The implementation of a multimodal, opioid-sparing protocol significantly reduces postoperative pain intensity, minimizes opioid consumption and related side effects, and improves patient satisfaction. These findings support the adoption of individualized, opioid-sparing strategies as a safe and effective standard for perioperative pain management.